An Analysis of Vocatives in Disney Movie Script: Descendants 2 - Sundara, Shafantya Fais; Fitriana, Kesi; Nurazni, Laeli (Faculty of Education and Teachers Training, 2024)
This research was conducted to find out vocative expressions used in the movie script Descendants 2. It is also carried out to identify the types of vocative expressions. This research was conducted by using descriptive qualitative method. The data of this research were taken from the dialogue containing vocative expressions in the movie entitled Descendants 2. They were classified by using Levinson theory. The result of this research shows that there are two types of vocatives used in Descendants 2 movie script, namely calls or summonses and addresses. Total items of vocative expressions used in Descendants 2 movie script are 222 items.Keywords: Vocative expressions, Descendants 2, movie script.